Antibiotic Production and Antibiotic Resistance: The Two Sides of AbrB1/B2, a Two-Component System of Streptomyces coelicolor - Sánchez de la Nieta, Ricardo; Antoraz, Sergio; Alzate, Juan F.; Santamaría, Ramón I.; Díaz, Margarita (Frontiers in Microbiology, 2020)
Antibiotic resistance currently presents one of the biggest threats to humans. The development and implementation of strategies against the spread of superbugs is a priority for public health. In addition to raising social awareness, approaches such as the discovery of new antibiotic molecules and the elucidation of resistance mechanisms are common measures. Accordingly, the two-component system of Streptomyces coelicolor AbrB1/B2, offer amenable ways to study both antibiotic production and resistance. Global transcriptomic comparisons between the wild-type strain S. coelicolor M145 and the mutant ΔabrB, using RNA-Seq, showed that the AbrB1/B2 two-component system is implicated in the regulation of different biological processes associated with stress responses, primary and secondary metabolism, and development and differentiation. The ΔabrB mutant showed the up-regulation of antibiotic biosynthetic gene clusters and the down-regulation of the vancomycin resistance gene cluster, according to the phenotypic observations of increased antibiotic production of actinorhodin and undecylprodigiosin, and greater susceptibility to vancomycin. The role of AbrB1/B2 in vancomycin resistance has also been shown by an in silico analysis, which strongly indicates that AbrB1/B2 is a homolog of VraR/S from Staphylococcus aureus and LiaR/S from Enterococcus faecium/Enterococcus faecalis, both of which are implied in vancomycin resistance in these pathogenic organisms that present a serious threat to public health. The results obtained are interesting from a biotechnological perspective since, on one hand, this two-component system is a negative regulator of antibiotic production and its high degree of conservation throughout Streptomyces spp. makes it a valuable tool for improving antibiotic production and the discovery of cryptic metabolites with antibiotic action. On the other hand, AbrB1/B2 contributes to vancomycin resistance and is a homolog of VraR/S and LiaR/S, important regulators in clinically relevant antibiotic-resistant bacteria. Therefore, the study of AbrB1/B2 could provide new insight into the mechanism of this type of resistance.